ANALISIS KINERJA KEUANGAN PT BANK RAKYAT INDONESIA (PERSERO), TBK - Sarida Sirait; Henry Dunan Pardede (Politeknik Bisnis Indonesia, 2020)
The Bank's Financial Performance Appraisal Method continues to evolve along with developments. This study aims to compare the level of financial performance of PT Bank Rakyat Indonesia (Persero) Tbk. in the period of Quarter I 2019 - Quarter II of 2020. The Bank's Financial Performance Level is measured through several assessments. These assessments include ratio assessments (ROA, ROE, NIM, BOPO). This research is a descriptive study with a quantitative approach. The subject of this research is the financial statements of PT Bank Rakyat Indonesia Tbk. (Persero). The object used in this research is the financial statements of PT Bank Rakyat Indonesia Tbk. (Persero) Quarter I 2019 - Quarter II 2020. The data collection technique in this study is by downloading financial reports from the official website of PT Bank Rakyat Indonesia Tbk. (Persero). The analysis technique used is the ratio assessment. The results of this study note that the Financial Performance Assessment of PT Bank Rakyat Indonesia Tbk. (Persero) with this ratio approach shows a continuing downward trend.